Rapamycin Regulates Bleomycin-Induced Lung Damage in SP-C-Deficient Mice - Madala, Satish K.; Maxfield, Melissa D.; Davidson, Cynthia R.; Schmidt, Stephanie M.; Garry, Daniel; Ikegami, Machiko; Hardie, William D.; Glasser, Stephan W. (Pulmonary Medicine, 2011)
Injury to the distal respiratory epithelium has been implicated as an underlying cause of idiopathic lung diseases. Mutations that result in SP-C deficiencies are linked to a small subset of spontaneous and familial cases of interstitial lung disease (ILD) and interstitial pulmonary fibrosis (IPF). Gene-targeted mice that lack SP-C (Sftpc-/-) develop an irregular ILD-like disease with age and are a model of the human SP-C related disease. In the current study, we investigated whether rapamycin could ameliorate bleomycin-induced fibrosis in the lungs of Sftpc-/- mice. Sftpc+/+ and −/− mice were exposed to bleomycin with either preventative administration of rapamycin or therapeutic administration beginning eight days after the bleomycin injury. Rapamycin-treatment increased weight loss and decreased survival of bleomycin-treated Sftpc+/+ and Sftpc-/- mice. Rapamycin did not reduce the fibrotic disease in the prophylactic or rescue experiments of either genotype of mice. Further, rapamycin treatment augmented airway resistance and reduced lung compliance of bleomycin-treated Sftpc-/- mice. Rapamycin treatment was associated with an increased expression of profibrotic Th2 cytokines and reduced expression of INF-γ. These findings indicate that novel therapeutics will be required to treat individuals with SP-C deficient ILD/IPF.